PENGARUH DIVERSIFIKASI PRODUK, HARGA, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN - Bima Akbar Ganata; Islamuddin Islamuddin (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2025)
Purchase decisions are one of the key factors determining the success of a business, especially in the food and beverage industry. This study aims to analyze the influence of product diversification, price, and promotion on customers' purchase decisions at Brens Bakery, Kota Manna, South Bengkulu. The research method used is quantitative with a survey approach. Data were collected through questionnaires distributed to Brens Bakery customers and analyzed using multiple linear regression techniques. The results indicate that product diversification has a positive and significant effect on purchase decisions, suggesting that the more diverse the products offered, the greater the likelihood of customers making a purchase. Price also has a positive and significant effect, meaning that appropriate pricing aligned with product quality and customers' purchasing power can enhance purchase decisions. Additionally, promotion has a positive and significant influence on purchase decisions, demonstrating that effective marketing strategies can increase product appeal and encourage customers to buy. This study confirms that product diversification, price, and promotion are the primary factors influencing customers' purchase decisions at Brens Bakery. Therefore, management is advised to continuously enhance product variety, set competitive prices, and optimize promotional strategies to increase customer purchases. Keywords: Product Diversification, Price, Promotion, Purchase Decision